Alkaline–Acid Zn–H2O Fuel Cell for the Simultaneous Generation of Hydrogen and Electricity. Issue 15 (25th January 2018) - Cai, Pingwei; Li, Yan; Wang, Genxiang; Wen, Zhenhai
Abstract: An alkaline–acid Zn–H2 O fuel cell is proposed for the simultaneous generation of electricity with an open circuit voltage of about 1.25 V and production of H2 with almost 100 % Faradic efficiency. We demonstrate that, as a result of harvesting energy from both electrochemical neutralization and electrochemical Zn oxidation, the as‐developed hybrid cell can deliver a power density of up to 80 mW cm −2 and an energy density of 934 Wh kg −1 and maintain long‐term stability for H2 production with an output voltage of 1.16 V at a current density of 10 mA cm −2 . Abstract : "Everything now" generation : An alkaline–acid Zn–H2 O fuel cell was developed for the simultaneous generation of electricity and H2 (see picture). The cell delivered an open‐circuit voltage of around 1.25 V with almost 100 % Faradic efficiency for H2 production and reached a power density of 80 mW cm −2 and an energy density of 934 Wh kg −1 .